Plan estratégico y su relación con el desarrollo empresarial de las asociaciones agrícolas de la parroquia El Rosario, cantón El Empalme, período 2014-2015. - Zambrano Vera, Eliana María (2015)
This research seeks to provide agricultural associations of the parish El Rosario a strategic plan that allows them to short, medium and long term development strategies that lead to better decisions within the guilds for managers to seek technical assistance to maintain a relationship direct and encourage SMEs to enable its partners to improve the income level. The research was structured as follows: CHAPTER I.- An analysis of the existing problems was made by a diagnosis of the causes and effect of the problem justifying percuten conducting such research through the definition of clear and precise objectives. CHAPTER II.- was based on the theory, concepts and laws that contributed to the development of research through texts relevant to the research authors. CHAPTER III.- This chapter describes the research methodology techniques, sources and bibliographical data allowed to establish a comprehensive and relevant research was designed....